Local-Culture-Based Materials in Online Cooperative Learning: Improving Reading Achievement in Indonesian Context - Hieronimus Canggung Darong (Journal of Innovation in Educational and Cultural Research, 2022)
The use of Cooperative Learning (CL) has attracted a great attention in the field. The aim of this study was to examine the effectiveness of CL in question along with local-culture-based materials toward students’ reading achievement. To achieve this goal, mixed method research design was employed incorporating cluster-random sampling technique of the third- grade- college students as the population. Post-test and interview were carried out to get the data which then were respectively analyzed statically and content analysis. The findings demonstrated that online Cooperative Learning (CL) along with local-culture-based materials was of benefit for better students’ reading achievement. This occurred as the pupils have good knowledge background to understand the texts in classroom activities. More importantly, students’ ability in predicting the idea of the text was better. To add the two essential features of CL, positive interdependence and individual accountability, text familiarity that so-called local-based-culture is demanded in implementing the online CL. In this respect, being cooperative does not solely guarantee successful learning. Content and text- familiarity are important to cope with.